Soy protein and chitin sponge-like scaffolds: from natural by-products to cell delivery systems for biomedical applications. Issue 11 (14th February 2020) - Las Heras, Kevin; Santos-Vizcaino, Edorta; Garrido, Tania; Borja Gutierrez, Francisco; Aguirre, Jose Javier; de la Caba, Koro; Guerrero, Pedro; Igartua, Manoli; Hernandez, Rosa Maria
Abstract : Natural and renewable resources, such as plant proteins and marine polysaccharides, to manufacture scaffolds with suitable properties for biomedical applications. Abstract : The increasing necessity of developing new devices for biomedical applications has added a growing social need of being environmentally respectful. In this work, we have shown that natural by-products from the food industry (soy protein and β-chitin) can be an excellent source of biomaterials to produce 3D scaffolds through simpler and cleaner processes. With the mixture of these two polymers, we have developed sponge-like scaffolds (SLS) with great physicochemical properties. Furthermore, a dialysis pre-conditioning step was enough to obtain negligible cytotoxicity in vitro . The predominant M2 macrophage profile, an elevated deposition of collagen fibres and the enhanced neovascularization capacity suggested excellent biocompatibility also in vivo . Moreover, these SLS were able to promote cell adhesion, proliferation and high loading capacity. Finally, h-MSCs 3D-cultured in these SLS released four times higher VEGF than h-MSCs seeded onto 2D plates. The green thinking strategy, properties and biocompatibility of this SLS highlight its potential as a cell delivery system for biomedical applications.